Clean and Healthy Living Behavior as Health Promotion for Stunting Prevention - Cinu, Surahman; Zainul; Febriyansyah Dermawan, Aji; Halima, Nur; Jannah, Raodatul; Zahraini, A; Jamaluddin, Indar Ismai (Teras Kampus as a member of PT Palem Edukasi Nusantara, 2024)
This community service aims to campaign for Clean and Healthy Living Behavior (PHBS) in an effort to prevent stunting of babies and toddlers in Ogolugus Village, Ampibabo District, Parigi Moutong Regency, Central Sulawesi Province. The community service (PKM) carried out is an educational health promotion campaign related to PHBS, namely environmental service, tree planting and plant maintenance, making vertical gardens, and environmental planning competitions to welcome World Food Day. Apart from that, assistance was also provided to the village of Posyandu with the installation of PHBS posters in the village meeting hall. It was concluded that health promotion activities regarding PHBS in Ogolugus Village had been carried out well and according to implementation targets. Activities can be carried out optimally because of the ease of obtaining the necessary tools and materials, as well as the support of the village government and community.